Oral probiotic extracellular vesicle therapy mitigates Influenza A Virus infection via blunting IL-17 signaling - Hongxia Zhou; Wenbo Huang; Jieting Li; Peier Chen; Lihan Shen; Wenjing Huang; Kailin Mai; Heyan Zou; Xueqin Shi; Yunceng Weng; Yuhua Liu; Zifeng Yang; et al. (Bioactive Materials)
The influenza A virus (IAV) damages intestinal mucosal tissues beyond the respiratory tract. Probiotics play a crucial role in maintaining the balance and stability of the intestinal microecosystem. Extracellular vesicles (EVs) derived from probiotics have emerged as potential mediators of host immune response and anti-inflammatory effect. However, the specific anti-inflammatory effects and underlying mechanisms of probiotics-derived EVs on IAV remain unclear. In the present study, we investigated the therapeutic efficacy of Lactobacillus reuteri EHA2-derived EVs (LrEVs) in a mouse model of IAV infection. Oral LrEVs were distributed in the liver, lungs, and gastrointestinal tract. In mice infected with IAV, oral LrEVs administration alleviated IAV-induced damages in the lungs and intestines, modified the microbiota compositions, and increased the levels of short-chain fatty acids in those organs. Mechanistically, LrEVs exerted their protective effects against IAV infection by blunting the pro-inflammatory IL-17 signaling. Furthermore, FISH analysis detected miR-4239, one of the most abundant miRNAs in LrEVs, in both lung and intestinal tissues. We confirmed that miR-4239 directly targets IL-17a. Our findings paved the ground for future application of LrEVs in influenza treatment and offered new mechanistic insights regarding the anti-inflammatory role of miR-4239.